Fortalecimiento de competencias científicas asociadas al desarrollo cognitivo de los estudiantes (2020)
The present work deals with the scientific abilities in primary basic and its incidence in the progress of their capacities and the academic processes of the students. The main objective of the study was to propose pedagogical strategies based on scientific competences for the cognitive development of students in primary basic education. A descriptive quantitative approach was considered, where a sample of 101 fifth-grade students and a group of 18 elementary school teachers was taken, to which surveys were applied, where it was obtained that, from the student perspective, low academic performance It is associated with the poor understanding of the topics developed as a consequence of the methodologies implemented in the classroom and from the teaching perspective, academic difficulties are associated with the poor development of cognitive processes at each educational level and the student's predisposition towards the academy. In correspondence to the above, the results indicate that in terms of scientific competences, students’ present limited performance in processes that demonstrate the understanding, construction and analysis of scientific knowledge and, from teaching practice, it is necessary to strengthen knowledge associated with practices. in the classroom and the strategies implemented in the classroom.